A critical Evaluation of Zakariyau Oseni’s (play in Arabic) Al-‘Amid Al-Mubajjal - Rahman, Lawal (Al-Adab Journal, 2022)
The emergence of Arabic play in Nigeria cannot be easily traced. However, the first published one is the Oseni’s al ’Amid al-Mubajjal (The Honorable Dean) in 1994.Thereafter, more than forty of the Nigerian Arabic plays have emerged. The aim of this study is to give a summarized translation of the play and critically examine its literary elements such as the themes, setting, characterization and plots as portrayed in the Arabic play. The research is also significant as it exposes the moral value of the play. The researcher used the descriptive method of research. The play is a reflection of what goes on in some Nigerian Universities where some students and staff are being oppressed by some wicked staff. Having examined the literary styles, it is found that literary elements are used by the author to a large extent to pilot the organic unity of the play. It is recommended, therefore, that the play should be staged on international television stations for the benefit of humanity.